Assessing efficiency of private shrimp seed producers in selected hatcheries of Peninsular Malaysia - Mohd Aripin, Mohd Ammarr (2013)
This study aims at estimating technical, allocative and cost efficiency of shrimp/prawn seed producers of Malaysia and determining costs and return in shrimp/prawn seed production. Data collected from 19 hatcheries (comprising 10 brackishwater shrimp hatcheries and 9 freshwater prawn hatcheries) from the states of Penang, Perak, Terengganu and Selangor were used in the study. Data Envelopment Analysis was applied to estimate efficiency scores of the hatcheries. Besides, cost, return and profitability of hatcheries was examined using farm management procedure. The TECRS (overall technical efficiency) was found to be 0.582 for brackishwater shrimp hatcheries and 0.692 for freshwater prawn hatcheries. Inefficiency associated with the overall technical efficiency was 42 percent for brackishwater shrimp hatchery and 31 percent for freshwater prawn hatcheries. Pure technical efficiency (TEVRS) averaged 0.907 for shrimp hatcheries and 0.918 for prawn hatcheries indicating that inefficiencies to the level of 9-10 percent do exist. The scale efficiency was even lower than pure technical efficiency. Thus, the overall level of inefficiencies could be reduced by operating at optimal scales and by eliminating pure technical inefficiencies via the adoption of the best practices of efficient hatcheries. Scale inefficiencies for the shrimp and prawn hatcheries make a greater contribution to overall inefficiency. Allocative efficiency (AE) and cost efficiencies (CE)were 0.78 and 0.70 for brackishwater shrimp hatchery and 0.79 and 0.73for freshwater prawn hatcheries suggesting that the realized level of spawn/fry could be produced by the hatcheries by spending 21.5 percent less on inputs. Ratios of technically efficient input quantity to cost efficient quantities were more than 1.00 for brood feed, spawn feed and labour for the two shrimp and prawn hatcheries. However, it was lower than 1.00 for electricity cost. Thus both types of hatcheries overused brood feed, spawn feed and labour while the electricity appeared to have been underused. Overshooting and undershooting of inputs was traced. Gross and net margins were positive. Benefit cost ratios of the shrimp and prawn hatcheries were more than 1.00 indicating that spawn/fry production was profitable in the short and long run.